The Emotional Timeline of Unemployment: Anticipation, Reaction, and Adaptation - Christian von Scheve; Frederike Esche; Jürgen Schupp (Institute for the Study of Labor (IZA), 2013)
Unemployment continues to be one of the major challenges in industrialized societies. Aside from its economic dimensions and societal repercussions, questions concerning the individual experience of unemployment have recently attracted increasing attention. Although many studies have documented the detrimental effects of unemployment for subjective well-being, they overwhelmingly focus on life satisfaction as the cognitive dimension of well-being. Little is known about the emotional antecedents and consequences of unemployment. We thus investigate the impact of unemployment on emotional well-being by analyzing the frequency with which specific emotions are experienced in anticipation of and reaction to job loss. Using longitudinal data of the German Socio-Economic Panel (SOEP) and fixed effects regressions, we find that becoming unemployed leads to more frequent experiences of unpleasant emotions only in the short run and that adaptation occurs more rapidly as compared to life satisfaction. Contrary to existing studies, we find decreases in emotional well-being but not in life satisfaction in anticipation of unemployment.
Keywords: A14; D63; J17; 330; unemployment; emotions; well-being; life satisfaction; SOEP